2009 2nd IEEE International Conference on Computer Science and Information Technology 2009
DOI: 10.1109/iccsit.2009.5234828
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent system for predicting Thrips tabaci Linde pest population dynamics allied to cotton crop

Abstract: The agricultural sector in India is up against a series of problems when it comes to increasing crop productivity. A number of successful researches have been carried out to discover productive agricultural practices to improve crop cultivation but despite their efforts, productivity achieved by most of the farmers has not been in upper-bound level. The prime reason stated globally for crop loss is Insect pests. An efficient pest management technique can be devised if we could predict in advance the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous studies have not adopted DT for S. dorsalis research. However, Patil et al (2009) employed ANNs for analyzing S. dorsalis data acquired from 2003 to 2008, showing that the correlation between the prediction results and the actual value was higher than 0.96. In our study, although the data were from a one-year period, we selected parts of the data as actual values for validation and demonstrated that the overall model derived from DT was superior to that derived from ANNs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies have not adopted DT for S. dorsalis research. However, Patil et al (2009) employed ANNs for analyzing S. dorsalis data acquired from 2003 to 2008, showing that the correlation between the prediction results and the actual value was higher than 0.96. In our study, although the data were from a one-year period, we selected parts of the data as actual values for validation and demonstrated that the overall model derived from DT was superior to that derived from ANNs.…”
Section: Discussionmentioning
confidence: 97%
“…The data of this study did not allow us to discuss the influence of pesticides on S. dorsalis population. Patil et al (2009) reported that highly accurate prediction results can help farmers manage pests, prevent crop loss, and reduce pesticide usage, and simultaneously mitigates environmental pollution. Nonetheless, future studies could focus on optimizing the accuracy of the prediction model by incorporating other variables that may influence the occurrence of S. dorsalis such as absolute humidity, dew point, saturation deficit, and sunshine ratio as suggested by Chang (1997).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations